2015
DOI: 10.1007/s00246-015-1217-2
|View full text |Cite
|
Sign up to set email alerts
|

Fontan Completion for Younger than 3 Years of Age: Outcome in Patients with Functional Single Ventricle

Abstract: Most single ventricle patients undergo Fontan procedure earlier in current era. However, optimal timing of Fontan completion after an intermediate staging surgery is controversial. We present children who had Fontan surgeries younger than 3 years of age comparing the data with older patients. Between 2000 and 2013, 45 patients with functional single ventricle underwent extracardiac total cavopulmonary connection (TCPC) using GORE-TEX(®) conduit at a single institution. Children were divided into group A (age <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In our group, 17 patients underwent extra-cardiac TCPC younger than 3 years of age. No significant difference was noticed in mortality and morbidity compared the outcome with the older patients [ 23 ]. This data corresponds with other authors’ results.…”
Section: Discussionmentioning
confidence: 99%
“…In our group, 17 patients underwent extra-cardiac TCPC younger than 3 years of age. No significant difference was noticed in mortality and morbidity compared the outcome with the older patients [ 23 ]. This data corresponds with other authors’ results.…”
Section: Discussionmentioning
confidence: 99%
“…Although the optimal timing of Fontan operation is still controversial, many contemporary centers aim to complete Fontan surgery in early childhood [4043]. Older age at Fontan operation is associated with lower exercise capacity [44,45] which could increase risk for excess weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the age of patients who have completed the Fontan procedure is younger than that in the past. For patients <15 years old, the outcomes of Fontan completion have not been related to age at operation . Saab and Aboulhosn reported that cyanotic adult single‐ventricle patients not palliated with Fontan completion preserved single‐ventricle systolic function but caused development of elevated ventricular filling pressure with increasing age.…”
Section: Discussionmentioning
confidence: 99%